Reference intervals for thyroid hormones for the elderly population and their influence on the diagnosis of subclinical hypothyroidism - Fu, Jingxuan; Wang, Peichang; Cao, Jingrong; Wang, Yidan; Liu, Yunyi; Song, Qinfei (Journal of Medical Biochemistry, 2022)
Purpose: To establish reference intervals (RIs) for thyroid hormones in the elderly population and analyze their influence on the prevalence of subclinical hypothyroidism. Patients and methods: Thyroid hormone records of subjects who underwent physical examination at our hospital between 2018 and 2020 were analyzed. Thyroid stimulating hormone (TSH), total triiodothyronine, total thyroxine, free triiodothyronine (FT3), and free thyroxine (FT4) levels were compared between young and elderly subjects. Thresholds of these thyroid hormones were established for elderly subjects. Results: A total of 24,209 subjects were included. Of them, 2,565 (10.6%) were aged ≥ 65 years. Elderly subjects had higher TSH, and lower FT3 and FT4 levels when compared with young subjects. In the elderly group, the RIs for TSH, FT3 and FT4 were 0.55–6.12 uIU/mL, 2.36–3.59 pg/mL, and 0.93–1.60 ng/dl, respectively. The age- and sex-specific RIs for TSH were 0.56-5.71 uIU/mL for men and 0.45-6.44 uIU/mL for women. With manufacturer-recommended RIs and our recommended age- and sex-specific RIs, the prevalence of subclinical hypothyroidism was 8.6% and 3.8% (p < 0.001), respectively. Conclusion: Elderly individuals had higher TSH levels than young individuals. Our study indicated that establishing specific RIs for elderly individuals is needed. This has implications for the diagnosis and management of subclinical hypothyroidism in the elderly population.